THE EFFECTIVENESS OF THE USE OF THE GOOGLE CLASSROOM APPLICATION IN LEARNING AQIDAH AKHLAK AT MADRASAH TSANAWIYAH AL-I'ANAH KOSAMBI - Asmanah, Siti; Hermawan, Iwan; Waloyo, Kasja Eki (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
The teaching and learning process that is usually carried out face-to-face must switch to online learning. This sudden change raises pros and cons in society, especially related to the effectiveness of online learning in achieving educational goals. One of the media that is widely used by teachers is Google Classroom. This study aims to examine the effectiveness of the use of Google Classroom in learning Aqidah Akhlak at MTs Al-I'anah Kosambi during the pandemic. The research method uses a descriptive approach with data collection techniques through observation, interviews, and questionnaires to teachers and students. Data analysis was carried out qualitatively by emphasizing the experience of using the application, the level of student involvement, and the perception of teachers and students on the usefulness of the media. The results of the study show that Google Classroom is quite effective in supporting the learning of Aqidah Akhlak during the pandemic. This application makes it easier for teachers to deliver materials and provide feedback, as well as allows students to access materials and assignments anytime and anywhere. However, several obstacles were found, including limited internet networks, lack of motivation for some students, and the need for teachers' adaptation in utilizing application features. However, in general, Google Classroom has been proven to support smooth online learning and make a positive contribution to the achievement of learning goals at MTs Al-I'anah Kosambi.